Analisis Penjabaran Transaksi Valuta Asing Pada PT Bank Central Asia Tbk Tahun 2022 Dan 2023 - Ayu, Nurmaya Ade Kresna; Kamilatuzzahirah, Siti Alifany; Mawarni, Rika; Pitriyani, Putri Rahayu; Rizki, Novia (Fakultas Ekonomi dan Bisnis Unram, 2024)
In practice, foreign currency transactions have the potential to generate foreign exchange differences (foreign exchange gain or loss) which can affect the company in terms of financial statements. Fluctuations This study aims to analyze the translation of foreign exchange transactions that occurred at PT BCA in 2022 and 2023. This research uses descriptive research methods using a quantitative approach, which is carried out by analyzing the financial statements of PT Bank Central Asia Tbk. in the period 2022 and 2023. The data in this study comes from secondary data obtained from the financial statements of PT Bank Central Asia. The results of this study are the determination of the functional currency and the translation process that occurs in the PT BCA company causing exchange rate differences presented in the equity group in the consolidated financial position in accordance with PSAK 221 regulations.